Pengaruh Kualitas Pelayanan Penggunaan Aplikasi Pospay Terhadap Loyalitas Pelanggan Studi KAsus PT. Pos Indonesia (Persero) Kantor Pos Cabang Probolinggo - murodah, hasilah; Kuthny, Abu Yazid; Kartika, Yenny (Sekolah Tinggi Ekonomi Islam Al-Furqon Prabumulih, 2024)
Businesses want to be aware of customer needs and desires in order to fulfill client expectations. Every consumer views the services they receive and their level of satisfaction varies, as does the Pospay application, a digital service application that is controlled by PT. Pos Indonesia. The purpose of this study is to evaluate the PosPay application's quality. services in the city of Probolinggo. Quantitative research methodology was employed in this investigation. Information in this research was collected by distributing questionnaires. The population and sample contained in this study, namely customers who use the pospay application in Probolinggo City, were sampled as many as 30 people. The sampling method uses saturated samples. Simple linear regression analysis is the data analysis method employed. The result showed that respondents responses to the quality of Pospay services at PT. Pos Indonesia (persero) Probolinggo City Branch, showed that respondents gave (positive) responses where the quality of the respondents physical evidence indicator was 0,588, norma residual was 0,030, reability was 0,770. This proves that the quality of Pospay services in the Probolinggo City Branch of PT. POS INDONESIA (persero). is good. Regarding respondents assessment of the quality of Pospay services at PT.Pos Indonesia Branch which is expected with the services received shows that respondents give respondents according to the expectation of the dimensions of 0.05